2021
DOI: 10.3390/ma14041010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Effect on the Microstructure and Hardness of AlMg3 Alloy under Upsetting

Abstract: To date, numerous investigations have shown the beneficial effect of ultrasonic vibration-assisted forming technology due to its influence on the forming load, flow stress, friction condition reduction and the increase of the metal forming limit. Although the immediate occurring force and mean stress reduction are known phenomena, the underlying effects of ultrasonic-based material softening remain an object of current research. Therefore, in this article, we investigate the effect of upsetting with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The hardness of the sample without ultrasonic treatment is 34.1 HB, while that of the sample treated for 120 min is 86.8 HB (Figure 3). The increase in alloy hardness due to ultrasonic treatment corresponds to the results of research on Ti-Al and Al-Mg alloys [10,11].…”
Section: Mechanical Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…The hardness of the sample without ultrasonic treatment is 34.1 HB, while that of the sample treated for 120 min is 86.8 HB (Figure 3). The increase in alloy hardness due to ultrasonic treatment corresponds to the results of research on Ti-Al and Al-Mg alloys [10,11].…”
Section: Mechanical Propertiessupporting
confidence: 72%
“…Research has been carried out to change the microstructure and improve the mechanical properties of Ti-Al and Al-Mg 3 alloys [ 10 , 11 ] and the shape memory effect via temperature variation or ultrasonic vibrations in the ultrasonic treatment of Ni-Ti SMAs [ 12 ]. Previous studies have shown that the thermal conductivity of Ni-Ti powder can be changed via ultrasonic vibrations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another method to make the thin-wall hollow structural components is the tube upsetting [ 21 , 22 ]. It can reduce the diameter of the tube through the mold [ 23 ].…”
Section: Introductionmentioning
confidence: 99%